A severe effect of anterior chest wall infection from odontogenic cause: Case Report - Karlin, Christiadi; Ariestiana, Yossi Y.; Ghazali, Mohammad (Hasanuddin University, 2025)
Objective: Odontogenic infections can be life-threatening if left untreated, those can spread multi- directional to superior, inferior, anterior, and posterior regions. It can travel down the neck to the supraclavicular fossa, axilla, and chest wall, potentially reaching the deltopectoral triangle. Immediate treatment is essential to prevent the infection from reaching the mediastinum. Methods: A 20 years old male presented to the ER at Hasanuddin University Hospital with swelling on the right cheek extended to chin, neck, and upper part of chest since 4 days before admission. He experienced diculty breathing and had a fever. Examination found tachypnea, tachycardia, fever 37.4Â°C, neck move limitation, mouth opening limitation, classical sign of inammation, and leukocytosis. Patient suspected as abscess of submandible extended to neck, andÂ chest. Incision and drainage accompanied with tooth extraction was performed and support therapy such as antibiotic treatment, nutritional support, extraoral massage, and chest compressive gauze. Results: The pleurovertebral and costopleural ligaments are key factors in determining whether infection in the deep neck fascial planes will spread to the mediastinum or the anterior chest wall. Strong ligaments direct the infection to the supercial chest wall, while weak ligaments allow the infection to spread deeper into the mediastinum. Conclusion: Comprehensive and rapid management of extraoral and intraoral drainage incisions and extraction of the causative tooth, chest compressive splinting and adequate medication and optimal nutritional therapy can prevent further spread of infection and provide a good prognosis.